Cover Image. Issue 1 (14th January 2020) - Png, Grace; Suveges, Daniel; Park, Young‐Chan; Walter, Klaudia; Kundu, Kousik; Ntalla, Ioanna; Tsafantakis, Emmanouil; Karaleftheri, Maria; Dedoussis, George; Zeggini, Eleftheria; Gilly, Arthur
Abstract : Front Cover Caption: The cover image is based on the Original Article Population‐wide copy number variation calling using variant call format files from 6, 898 individuals by Arthur Gilly et al., https://doi.org/10.1002/gepi.22260 .